THE EFFICACY OF GAMIFICATION IN ENHANCING VOCABULARY ACQUISITION AMONG SECONDARY LEVEL ESL LEARNERS - Umaraliyev Mukhriddin (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the intersection of Ludic Pedagogy and Second Language Acquisition  (SLA).  As  traditional  rote  memorization  faces  criticism  for  low engagement  levels,  gamification—the  application  of game-design  elements  in  non-game  contexts—offers  a  promising  alternative.  This  study  examines  how  digital platforms such as Kahoot! and Quizlet impact lexical retention and student motivation.